THE EXTRACT OF PURPLE SWEET POTATO DECREASE BLOOD AND LIVER MDA OF MICE AFTER INTENSE PHYSICAL ACTIVITY - Jawi, I Made; Suprapta, Dewa Ngurah; Ngurah Subawa, A.A. (Jurnal Veteriner; Vol 9 No 2 (2008), 2008)
Oxidative stress as consequence of intense physical exercises cause tissue lesions. The objective of this study was to identify the comparable antioxidant effect of water extract and syrup of Balinese purple sweet potato to the liver tissue in mice after maximal exercise, through the quantification of blood and liver malondialdehyde (MDA), and the histologic feature of liver tissue. Subjects of this study were 60 adult male Swiss mice divided into 6 groups with control group post-test only design. Blood and liver were collected after exercise protocol of exhausting swimming in ten mice without water extract, ten mice with water extract and ten mice with syrup of Balinese purple sweet potato. The MDA was quantification with TBARS method. Samples were also collected from control group of ten mice without water extract, ten mice with water extract and ten mice with syrup of Balinese purple sweet potato as sedentary mice. The results show a significant increase of MDA in the blood and liver, after swimming with and without water extract or syrup of Balinese purple sweet potato respectively (p<0,05). The increase of MDA was slightly significant in the group with water extract or syrup of Balinese purple sweet potato (p<0,05). The increase of liver cell necrosis was slightly significant in the group with water extract of Balinese purple sweet potato (p<0,05). From this finding it can be concluded that water extract or syrup of Balinese purple sweet potato has antioxidant effect in exhausting exercise in mice. Water extract of Balinese purple sweet potato has protective effect to the liver cell in exhausting exercise in mice
Keywords: Oxidative stress, Balinese purple sweet potato, liver, MDA, mice